The Oleo-Gum-Resin of Commiphora myrrha Ameliorates Male Reproductive Dysfunctions in Streptozotocin-Induced Hyperglycemic Rats - Mohammadmehdi Hassanzadeh_Taheri; Mehran Hosseini; Davood Dorranipour; Mohammad Afshar; Hesam Moodi; Mojtaba Salimi (Tabriz University of Medical Sciences, 2019)
Background: The oleo-gum-resin of Commiphora myrrha (myrrh) has a long history of therapeutic use in traditional medicine. The aim of this study was to seek for the scientific evidence to determine whether the ethanolic extract of myrrh (EEM) has any beneficial effects on Streptozotocin (STZ) induced testicular impairments, and explore the possible mechanisms underlying such actions. Methods: Forty-eight severe and complicated diabetic rats (fasting blood glucose above 350 mg/dL), randomly were divided into six equal groups (n=8). Besides, eight healthy rats allocated as a normal control group and only treated with vehicle solution. The diabetic animals orally received the extract (100, 200, 300, and 500 mg/kg), metformin (500 mg/kg) or vehicle solution for 28 days. As a final point, plasma glucose and insulin, circulatory sex hormones, sperm parameters including sperm concentration, motility and viability and also testicular malondialdehyde (MDA) levels were assessed. Furthermore, quantitative histological evaluation of seminiferous tubules area and determination of germinal cells apoptosis were performed. Results: None of the studied doses of EEM showed anti-diabetic effects. However, the extract mainly at the maximum dose (500 mg/kg) exhibited beneficial effects on reproductive impairments. The EEM treated rats mainly at 500 mg/kg had significantly higher sperm concentration, sperm motility, sperm viability, sex hormones and lower testicular MDA and germ cell apoptosis index than untreated diabetic rats. Conclusion: These results indicated that EEM may have beneficial effects against reproductive dysfunction induced by diabetes. The mechanisms behind the effects might be associated with the EEM sex hormone booster potential, antioxidant and anti-apoptotic properties.